Aktivitas Antiviral Minyak Atsiri Jahe Merah terhadap Virus Flu Burung (ANTIVIRAL ACTIVITY OF ESSENSIAL OIL RED GINGER ON AVIAN INFLUENZA) - Untari, Tri; Widyarini, Sitarina; Wibowo, Michael Haryadi (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
The studies have reported that ginger have many activities such as antiemesis, anti-inflammatory,anti-bacterial and anti-parasites. Therefore, this study was conducted to evaluate antiviral effect of essentialred ginger oil againts Avian Influenza (AI) in ovo using hemagglutination test (HA). Avian Influenzaviruses were treated with 0,01%, 0,1% and 1% of essential red ginger oil, and then inoculated in chickenembryonated egg via allantoic sac. Allantoic fluid was harvested using for HA test . Result of this studyshows that application of 1% of essential red ginger oil results in the reduction of titer HA . Interestingly,essential oil shows antiviral activity revealed HA titre 20 whereas the titre HA AI which AI virus treatedwith 0,01% and 0,1% essential red ginger oil, the HA titer was 25. The conclution of this study proved thatessensial oil 1% of the red gingger is the best concentration as antiviral activity .
Keywords: red ginger, antiviral avian influenza , hemagglutination test